Donor Site Morbidity of Patients Receiving Vertical Rectus Abdominis Myocutaneous Flap for Perineal, Vaginal or Inguinal Reconstruction - Schellerer, Vera; Bartholomé, Lenka; Langheinrich, Melanie; Grützmann, Robert; Horch, Raymund E.; Merkel, Susanne; Weber, Klaus (World Journal of Surgery, 2020)
Background: Management of donor site closure after harvesting a vertical rectus abdominis myocutaneous (VRAM) flap is discussed heterogeneously in the literature. We aim to analyze the postoperative complications of the donor site depending on the closure technique. Methods: During a 12-year period (2003–2015), 192 patients in our department received transpelvic VRAM flap reconstruction. Prospectively collected data were analyzed retrospectively. Results: 182 patients received a VRAM flap reconstruction for malignant, 10 patients for benign disease. The median age of patients was 62 years. 117 patients (61%) received a reconstruction of donor site by Vypro® mesh, 46 patients (24%) by Vicryl® mesh, 23 patients (12%) by direct closure and 6 patients (3%) by combination of different meshes. 32 patients (17%) developed in total 34 postoperative complications at the donor site. 22 complications (11%) were treated conservatively, 12 (6%) surgically. 17 patients (9%) developed incisional hernia during follow-up, with highest incidence in the Vicryl® group (n = 8; 17%) and lowest in the Vypro® group (n = 7; 6%). Postoperative parastomal hernias were found in 30 patients (16%) including three patients with simultaneous hernia around an urostomy and a colostomy. The highest incidence of parastomal hernia was found in patients receiving primary closure of the donor site (n = 6; 26%), the lowest incidence in the Vypro® group (n = 16; 14%). Conclusion: The use of Vypro® mesh for donor site closure appears to be associated with a low postoperative incidence of complications and can therefore be recommended as a preferred technique.
CRIS-Team Scopus Importer:2020-10-09